Disseminated tuberculosis with immune thrombocytopenic purpura - Dagaonkar, Rucha S. (Medknow Publications & Media Pvt Ltd, 2012)
Tuberculosis has a variety of hematological manifestations. Immune thrombocytopenic purpura is an uncommon manifestation of tuberculosis. We present a case of disseminated tuberculosis with isolated thrombocytopenia. While TB granulomas in the bone marrow can themselves cause hematological abnormalities, persistent thrombocytopenia refractory to anti-TB therapy may be ITP associated with TB.